Translation and validation of Malay version of NIOSH worker well-being questionnaire (WellBQ) - Nionella Stephen Sampil; Aziah Daud; Suhaily Mohd Hairon (PLoS ONE, 2025)
The NIOSH Worker Well-Being Questionnaire (WellBQ) offers a comprehensive framework to evaluate worker well-being across five domains: work evaluation, workplace policies, physical environment and safety, health status, and home/community influences. In Malaysia, traditional occupational safety and health (OSH) initiatives have primarily focused on workplace hazards, often neglecting broader psychosocial and organizational factors. To address this gap, this study adapted and validated the Malay version of the WellBQ for healthcare workers, ensuring cultural and contextual relevance. A rigorous translation process, including forward and backward translation, expert panel reviews, and pilot testing, was conducted to retain the original framework while addressing local nuances. Psychometric evaluation involved 366 healthcare workers from Hospital Universiti Sains Malaysia, employing Confirmatory Factor Analysis (CFA) to assess model fit, internal consistency, and construct validity. The Malay WellBQ demonstrated robust psychometric properties, with a Content Validity Index (CVI) of 0.92 and a Face Validity Index (FVI) of 0.98, reflecting high relevance and clarity. CFA confirmed an acceptable model fit (RMSEA = 0.050, CFI = 0.887, TLI = 0.877) and strong internal consistency (CR > 0.7). Convergent validity was observed across most subdomains, although some Average Variance Extracted (AVE) scores fell below 0.5, highlighting areas for refinement. Discriminant validity was achieved within domains but revealed overlaps between some domains, suggesting interconnected constructs. The Malay WellBQ is a reliable and culturally relevant tool for assessing worker well-being, offering actionable insights for workplace policy and intervention development. Further refinements are recommended to enhance construct validity across domains.